Multicultural Education: Building Inclusive Attitudes in Diversity - Aulia Rabbani, Syarifah; Addarunnasfis, Muh.; Malik, Asriati Aulia (Schemata: Jurnal Pascasarjana UIN Mataram, 2025)
This study uses a descriptive qualitative method, which aims to explore the roles of schools, teachers and parents in building inclusive attitudes in students. Inclusive attitudes are developed through formal education at school and character education at home. Schools and teachers play an important role in providing multicultural education that aims to shape students to appreciate diversity and be able to interact in a plural society. In addition, schools are also responsible for creating an inclusive learning environment and providing training to teachers to improve their understanding of multicultural education. Steps taken include implementing an inclusive curriculum, organizing extracurricular activities that encourage intercultural interaction, using multiple languages in learning, character development and community activities. Parents also play a significant role in character education at home, serving as primary educators who model inclusive attitudes. Students' own awareness is also a key factor for inclusive and multicultural education to be well established through learning experiences and social interactions inside and outside school. Keywords: Inclusiveness, Multicultural Education, Diversity Penelitian ini bertujuan untuk mengeksplorasi peran sekolah, guru, dan orang tua dalam membangun sikap inklusif pada siswa. Sikap inklusif dikembangkan melalui pendidikan formal di sekolah dan pendidikan karakter di rumah. Penelitian ini menggunakan metode kualitatif deskriptif untuk melihat dan menguraian secara jujur bagaimana kondisi riil di lapangan. Sehingga hasil penelitian mengungkapkan bahwa Sekolah dan guru berperan penting dalam memberikan pendidikan multikultural yang bertujuan membentuk siswa agar menghargai keberagaman dan mampu berinteraksi dalam masyarakat yang plural. Selain itu, sekolah juga bertanggung jawab menciptakan lingkungan belajar yang inklusif serta memberikan pelatihan kepada guru untuk meningkatkan pemahaman tentang pendidikan multikultural. Langkah-langkah yang diambil meliputi penerapan kurikulum inklusif, penyelenggaraan kegiatan ekstrakurikuler yang mendorong interaksi antarbudaya, penggunaan berbagai bahasa dalam pembelajaran, pengembangan karakter, dan kegiatan komunitas. Orang tua juga memiliki peran signifikan dalam pendidikan karakter di rumah, berfungsi sebagai pendidik utama yang memberikan teladan sikap inklusif. Kesadaran dari siswa sendiri juga menjadi faktor kunci agar pendidikan inklusif dan multikultural dapat terbentuk dengan baik melalui pengalaman belajar serta interaksi sosial di dalam dan luar sekolah. Kata kunci: Inklusivitas, Keberagaman, Pendidikan Multikultural